Physical violence against health staff by mentally ill patients at a psychiatric hospital in Botswana - Anthony A. Olashore; Oluyemi O. Akanni; Radiance M. Ogundipe (BMC, 2018)
Abstract Background Workplace violence is worrisome in the mental health sector. Little is understood about it in sub-Saharan Africa. Consequently, we decided to investigate the prevalence, related factors, and the available sources of support for the victims of workplace violence in a mental referral hospital in Botswana. Methods We conducted a cross-sectional retrospective survey of 201 mental health staff (MHS) of Sbrana Psychiatric Hospital, Botswana. We used a self-administered questionnaire to obtain information on socio-demographics and various aspects of work-related violence and available source of supports. We also used Andrew and Withey Job Satisfaction Questionnaire to assess the workers' level of job satisfaction. Results One hundred and seventy-nine questionnaires out of the two hundred and one returned were analyzed. One hundred and twenty-five (69.8%) of the respondents reported a lifetime experience of physical violence, while 44.1% experienced the same during the previous 12 months. Nursing services (χ2 = 29.95, p < 0.01) and long duration of service (χ2 = 29.95, p < 0.01) were associated with lifetime encounter of physical violence. Those who reported a physical assault had a higher level of job dissatisfaction than staff who never experienced violence (t = − 3.07, p = 0.02). Conclusions The rate of physical violence among mental health workers in Botswana is comparably high, and nurses are the most exposed members of staff. Protocol development and periodic training on violence prevention are hence recommended, especially for the most exposed members of staff.